TRAFFIC GUIDANCE SERVICES IN THE SULUT REGIONAL POLICE AREA TO BUILD A CULTURE OF ORDER ON SCHOOL STUDENTS - Mongkareng , Steven; Rawis, Joulanda M.; Jacobus, Suzan (Journal of Higher Education and Academic Advancement, 2024)
Objectivein this research is on managementtraffic community services in the North Sulawesi Regional Police Area to build a culture of order among school students, withuses management functions, namely planning, organizing, implementing and evaluating. The research method used was descriptive qualitative which was carried out in 2022 - 2023 in the North Sulawesi Provincial Police Area and Manado State University using the techniquetriangulation data collection. The research results showNorth Sulawesi Regional Police to build a culture of orderly trafficstarting from Elementary School regarding the introduction of traffic signs and for school material in Middle & High School/Senior High School. InManagement organizingNot all schools have visits or socialization for students at school and if there is socialization and policing, it is not carried out regularly, but there are several schools where during orientation new students provide material about the culture of orderly traffic.The implementation of service management to date still has many deficiencies in students' understanding of the culture of orderly traffic, which can only be obtained from teachers who deliver material on this matter. Evaluation of traffic community service management in the North Sulawesi Regional Police Area to build a culture of orderly traffic in the communityNow in the future the school plans to include it in the school curriculum material and will socialize the culture of orderly traffic to students by inviting the police as resource persons